Photocatalytic Activity and Characterization of Carbon-Modified Titania for Visible-Light-Active Photodegradation of Nitrogen Oxides. (8th February 2012) - Huang, Chun-Hung; Lin, Yu-Ming; Wang, I-Kai; Lu, Chun-Mei
Abstract : A variety of carbon-modified titania powders were prepared by impregnation method using a commercial available titania powder, Hombikat UV100, as matrix material while a range of alcohols from propanol to hexanol were used as precursors of carbon sources. Rising the carbon number of alcoholic precursor molecule, the modified titania showed increasing visible activities of N O x photodegradation. The catalyst modified with cyclohexanol exhibited the best activities of 62%, 62%, 59%, and 54% for the total N O x removal under UV, blue, green, and red light irradiation, respectively. The high activity with long wavelength irradiation suggested a good capability of photocatalysis in full visible light spectrum. Analysis of UV-visible spectrum indicated that carbon modification promoted visible light absorption and red shift in band gap. XPS spectroscopic analysis identified the existence of carbonate species (C=O), which increased with the increasing carbon number of precursor molecule. Photoluminescence spectra demonstrated that the carbonate species suppressed the recombination rate of electron-hole pair. As a result, a mechanism of visible-light-active photocatalyst was proposed according to the formation of carbonate species on carbon-modified TiO2 .